Settlement of Remaining Financing Due to Rejected Insurance Claims from the Perspective of POJK Number 69/POJK.05/2016 (Case Study at BPRS Puduarta Insani Medan) - Siregar, Hotma Sari; Zahara, Fatimah (AL-IKTISAB: Journal of Islamic Economic Law, 2024)
Insurance constitutes a risk transfer mechanism or a contractual agreement among multiple parties, wherein the insurer obligates itself to the insured by accepting a premium in exchange for compensation related to losses, damages, or anticipated profit losses. This research aims to identify the factors contributing to customer claim failures and to understand the resolution of issues faced by customers at BPRS Puduarta Insani Medan. The text subsequently details the resolution of the outstanding insurance claim payment financing that was denied at BPRS Puduarta Insani Medan, analyzed in accordance with POJK Number 69/POJK.05/2016. The author utilizes the empirical legal research method in this study, incorporating data collection techniques including direct interviews and observation within the company. This is subsequently presented as descriptive report. The customer's claim was unsuccessful due to their failure to comply with the pertinent legal provisions. BPRS Puduarta Insani Medan discovered that the customer had acted dishonestly by concealing their ailment from the bank when insuring themselves as a customer. The customer's claim failure at BPRS Puduarta Insani Medan was resolved as a consequence of data manipulation disguised as a health history letter. As a result, the bank and the heirs achieved an agreement that the payment would continue and be settled by the heirs, as it was not regulated in the agreement regarding the customer's demise. POJK Number 69/POJK.05/2016 has established a comprehensive framework for safeguarding the interests of financing companies and the heirs of customers when navigating delicate and intricate circumstances, such as the passing of a debtor. Heirs should carefully examine the financing agreement and the relevant insurance policy to confirm their obligations and rights in these circumstances.